Hambatan Guru Matematika dalam Mengimplementasikan Kurikulum Merdeka: Systematic Literature Review - Ahmad Mukhibin; Bashirotun Nafidhoh (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2023)
This study aims to describe the obstacles of mathematics teachers in implementing the Merdeka curriculum. The research method used a systematic literature review using the PRISMA protocol. There were 9 research articles published in 2022-2023 which were used as research samples. The articles were then analyzed by categorizing based on the year of research, type of research, research instruments used, research location, and types of obstacles faced by mathematics teachers. The findings of this study show that (1) the obstacles faced by mathematics teachers in 2023 increased from the previous year, (2) 88.8% of the articles used qualitative research to reveal the obstacles of mathematics teachers, (3) 6 articles preferred to use interview instruments, (4) the obstacles in implementing the Merdeka curriculum were felt by several mathematics teachers in various regions, and (5) the obstacles of mathematics teachers in implementing the Merdeka curriculum lie in the planning, implementation, and assessment stages of learning. The findings of this study are expected to be able to contribute and provide input to relevant government agencies to prepare the competence of mathematics teachers in implementing the Merdeka curriculum.